2015
DOI: 10.5152/tjg.2015.6043
|View full text |Cite
|
Sign up to set email alerts
|

Use of internet resources by patients awaiting gastroenterology consultation

Abstract: Background/Aims: The purpose of this study is to understand how outpatients awaiting initial gastroenterology consultation seek medical information on the Internet and how wait times affect Internet usage. Materials and Methods: A cross-sectional survey of 87 gastroenterology outpatients awaiting consultation was performed at a tertiary care center. Results: Fifty-two patients (60%) utilized the Internet for medical information. The mean age of patients using the Internet was 41 years, whereas the mean age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Teriaky et al [40] surveyed patients (N=87) awaiting appointments at a general gastroenterology clinic and asked those who reported using the Web prior to their consultations whether this had changed their anxiety levels. In all, 77% experienced no change, 21% experienced an increase, and 2% a decrease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teriaky et al [40] surveyed patients (N=87) awaiting appointments at a general gastroenterology clinic and asked those who reported using the Web prior to their consultations whether this had changed their anxiety levels. In all, 77% experienced no change, 21% experienced an increase, and 2% a decrease.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that using the Web to appraise symptoms causes anxiety, or that anxiety triggers Web use for symptom appraisal, or that a third factor influences both. Furthermore, the surveys that reported on anxiety among online self-diagnosers were biased toward certain demographic [42] or patient groups [40], and did not use validated measures of anxiety levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, people tend to use the internet for determining whether or not they should consult a physician [2]. Younger patients, females, and highly educated individuals are known to search for health information more often than others [3,4]. Internet use has the potential to improve patient empowerment, as well-informed patients tend to play a more active role in their own health care [5].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Similar prior studies found as many as >90% of patients presenting to various outpatient gastroenterology clinics reporting Internet usage for obtaining health-related information, but only a small proportion did so based on advice from their physician. [ 7 8 9 10 11 12 13 ] Therefore, searching the Internet without guidance to the websites with high-quality content may leave patients vulnerable to misleading and deceptive information and jeopardize their informed decision-making process.…”
Section: Introductionmentioning
confidence: 99%